Exploring brain perfusion in dogs with meningoencephalitis of unknown origin: A promising role for arterial spin labeling imaging - Léa Arti; Kirsten Gnirs; Stella Papageorgiou; Yannick Ruel; Albert Agoulon; Nathalie Boddaert; Hugues Gaillot (Journal of Veterinary Internal Medicine)
Abstract Background Arterial spin labeling (ASL) is a noninvasive brain perfusion magnetic resonance imaging (MRI) technique that has not been assessed in dogs with meningoencephalitis of unknown origin (MUO). Hypothesis/Objectives Assess brain perfusion changes characteristics before and after medical treatment, and investigate the role of ASL perfusion in the diagnosis and prognosis of MUO in dogs. Animals Thirty‐one dogs with presumed MUO. Methods Prospective study. Each animal had brain MRI including standard and ASL perfusion sequences at presentation and after treatment of 3 months or longer. Brain perfusion characteristics were assessed visually and by cerebral blood flow (CBF) measurements. Perfusion characteristics were compared pre‐ and post‐treatment. Results Dogs with MUO had preferential localization of lesions in optic nerves (ONs) and brainstem. At presentation, one third of the dogs with MUO had focal brain perfusion alterations and two‐thirds had global brain hypoperfusion. Both focal and global brain perfusion changes resolved after treatment in all surviving dogs. Arterial spin labeling failed to predict prognosis. Conclusions and Clinical Importance Brain ASL perfusion in dogs with MUO demonstrated the value of ASL in the diagnosis and follow‐up of the condition, suggesting the value of adding ASL to the clinical evaluation in dogs with suspected MUO. Preferential lesion localization in ON and brainstem resembled findings in the central nervous system of human patients with inflammatory demyelinating diseases. Future studies with histopathological confirmation are needed to better characterize the benefits of ASL in the different subtypes of non‐infectious encephalomyelitis in dogs.